The Purification of Human Prothrombin - Shapiro, S. S; Waugh, D. F (Thrombosis and Haemostasis, 1966)
A method has been presented for the preparation of human prothrombin. The product is apparently homogenous by chromatographic, ultracentrifugal, electrophoretic and immunochemical analysis. It contains less than 1 part in 107 of thrombin and has a specific activity of 1560 u/mg dry weight. Problems related to the variability in specific activity of prothrombin preparations reported in the literature have been critically reviewed.